A user interface / user experience with the sprint google design and a / b testing at the website startup qtaaruf - aditya anugrah pratama; Pantjawati Sudarmaningtyas; Sri Hariani Eko Wulandari (Jurnal Sistem Informasi Universitas Dinamika, 2018)
Qtaaruf is a startup from Surabaya that using a website as the media for interaction between users. The website now has around 10-20 visitors every day, it is classified as low visit for a website, because the inaccuracy of the user interface/user experience. This research is purposed to deliver a user interface and friendly user experience for the users in order to get information from the website, by using google design sprint that consist of 5 stages that are understand, diverge, decide, prototype, and validate. Validating process using a/b testing with 100 single moslem respondents in Surabaya at age range around 20-29. Based on the analysis, implementation and evaluation, resulting a final prototype, combination of A and B prototype which was validated form interface, use duration, and consideration of critique and feedback. Prototype A has been chosen for 4 features namely sign-up with 68,75% of the result, gallery, testimony, and taaruf process with 100%. Prototype B for the features of subscribtion with 100% of result. Prototype final delivers the user interface with colours harmony, consistency of layout, including notification for every interaction and user experience that match with respondent’s mindset for getting the information or reaching the objective.